Multiple change point analysis of hepatitis B reports in Xinjiang, China from 2006 to 2021 - Liping Yang; Liping Yang; Na Xie; Yanru Yao; Chunxia Wang; Ramziya RiFhat; Maozai Tian; Kai Wang (Frontiers Media S.A., 2023)
ObjectiveHepatitis B (HB) is a major global challenge, but there has been a lack of epidemiological studies on HB incidence in Xinjiang from a change-point perspective. This study aims to bridge this gap by identifying significant change points and trends.MethodThe datasets were obtained from the Xinjiang Information System for Disease Control and Prevention. Change points were identified using binary segmentation for full datasets and a segmented regression model for five age groups.ResultsThe results showed four change points for the quarterly HB time series, with the period between the first change point (March 2007) and the second change point (March 2010) having the highest mean number of HB reports. In the subsequent segments, there was a clear downward trend in reported cases. The segmented regression model showed different numbers of change points for each age group, with the 30-50, 51-80, and 15-29 age groups having higher growth rates.ConclusionChange point analysis has valuable applications in epidemiology. These findings provide important information for future epidemiological studies and early warning systems for HB.